Hydrogen bonding networks in gabapentin protic pharmaceutical salts: NMR and in silico studies. (17th December 2018) - Martins, Inês C.B.; Sardo, Mariana; Čendak, Tomaž; Gomes, José R.B.; Rocha, João; Duarte, M. Teresa; Mafra, Luís
Abstract: Hydrogen bonds (HBs) play a key role in the supramolecular arrangement of crystalline solids and, although they have been extensively studied, the influence of their strength and geometry on crystal packing remains poorly understood. Here we describe the crystal structures of two novel protic gabapentin (GBP) pharmaceutical salts prepared with the coformers methanesulfonic acid (GBP:METHA) and ethanesulfonic acid (GBP:ETHA). This study encompasses experimental and computational electronic structure analyses of 1 H NMR chemical shifts (CSs), upon in silico HB cleavage. GBP:METHA and GBP:ETHA crystal packing comprise two main structural domains: an ionic layer (characterized by the presence of charge‐assisted + NHGBP ⋯O − METHA/ETHA HB interactions) and a neutral layer generated in a different way for each salt, mainly due to the presence of bifurcated HB interactions. A comprehensive study of HB networks is presented for GBP:METHA, by isolating molecular fragments involved in distinct HB types (NH⋯O, OH⋯O, and CH⋯O) obtained from in silico disassembling of an optimized three‐dimensional packing structure. Formation of HB leads to calculated 1 H NMR CS changes from 0.4 to ~5.8 ppm. This study further attempts to assess how 1 H NMR CS of protons engaged in certain HB are affected when other nearby HB, involving bifurcated or geminal/vicinal hydrogen atoms, are removed. Abstract : Studying hydrogen bond interactions by in silico disassembling of the anticonvulsant gabapentin 3D structure.